2006
DOI: 10.1007/s00467-006-0052-3
|View full text |Cite|
|
Sign up to set email alerts
|

Lupus nephritis in Chinese children – a territory-wide cohort study in Hong Kong

Abstract: We report a multicenter study of Chinese children in Hong Kong with systemic lupus erythematosus (SLE) nephritis. Children were included if: they fulfilled the ACR criteria, had significant proteinuria or casturia, were Chinese and younger than 19 years and had been diagnosed with SLE between January 1990 and December 2003. Investigators in each center retrieved data on clinical features, biopsy reports, treatment and outcome of these patients. There were 128 patients (eight boys, 120 girls; mean age: 11.9+/-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
38
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 27 publications
10
38
5
Order By: Relevance
“…This might reflect the less percent of glomeruli with crescents and those with global sclerosis in the LN group. Similar good renal outcome was reported by others [1012] (Table 8). In one study, [10] none of the children with lupus nephritis required dialysis which is similar to our finding (Table 8).…”
Section: Discussionsupporting
confidence: 90%
“…This might reflect the less percent of glomeruli with crescents and those with global sclerosis in the LN group. Similar good renal outcome was reported by others [1012] (Table 8). In one study, [10] none of the children with lupus nephritis required dialysis which is similar to our finding (Table 8).…”
Section: Discussionsupporting
confidence: 90%
“…Septicemia occurring on a background of ESRD or otherwise was the commonest cause of death (75%). Other previous Indian studies and studies from other developing countries (Table 4) have also reported a similar trend wherein most children with lupus nephritis succumbed to serious infections (11,18,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 72%
“…Lupus nephritis (LN) is one of the most severe complications, drastically increasing the morbidity and mortality of SLE patients 6 , with up to 60% of adult and 80% of pediatric SLE cases developing renal abnormalities during the course of the disease 7; 8 . The incidence of LN is higher in AA, HI and AS compared to populations of European ancestry: one study showed that incidences of renal disease for AA and HI are 68.9% and 60.6% respectively compared to EA (29.1%) after 5.5 years of follow-up 9 ; a similar elevated incidence in AS has also been confirmed 10;11 .…”
Section: Introductionmentioning
confidence: 94%